Articles Published in all issues in 2010 in Sport Mont Journal: A Content Analysis - Marko Knezevic (Journal of Anthropology of Sport and Physical Education)
Sport Mont Journal (SMJ) is a print and electronic scientific journal. Sport Mont Journal is published three times a year by the Montenegrin sport academy (MSA), in February, June and October of each year. To this day, close to 1,000 scientific papers of researches from all continents have been published in it. These are mostly papers presented at the scientific conferences of the Montenegrin Sports Academy, which are traditionally held every year at the end of March or early April. Sport Mont Journal covers all aspects of sports science and medicine; health and sport; exercise physiology and biophysical investigation of sports performance; physical culture; sports nutrition; rehabilitation; sports psychology; sport pedagogy; sport history sport philosophy; social and humanistic side etc. In this paper work which is about A Content Analysis of Published Articles in Sport Mont Journal in 2010. In such a way that all works will be selected according to the respective scientific fields to which they belong. This paper work presents the table with titles of the scientific fields according to which the works were sorted and their exact number. In the subtitle, the results are all assigned to all the works that have been processed and, in the end, the subheading entitled discussion gives a brief overview of the results obtained.